Analisis Yuridis Sengketa Penggunaan Hak Paten Invensi Alat Sterilisasi Tandan Kelapa Sawit (Putusan MA Nomor 1130K/PDT.SUS-HKI/2021) - Aulida, Dinda; Saidin, Saidin; Leviza, Jelly (JUNCTO: Jurnal Ilmiah Hukum, 2024)
This article or paper aims to analyze the patent's legal protection for the palm bunch sterilizer according to Law Number 13 of 2016 as well as the reasons for the rejection of the patent holder's lawsuit and legal considerations in the Supreme Court Decision 1130K/2021. This study uses a normative juridical method with a legislative approach and analysis of legal concepts. The source includes primary legal materials, namely Law Number 13 of 2016 concerning Patents, and secondary literature related to Patent Rights and Unlawful Acts. This article analyzes the legal protection of the patent for palm bunches sterilizer based on Law Number 13 of 2016 and legal considerations in Supreme Court Decision 1130K/2021. The research uses a normative juridical method with primary legal materials and secondary literature related to Patent Rights. The results confirm that the patent is the exclusive right of the inventor to use or license his invention. In infringement cases, the patent owner can sue for damages, even though public understanding of patent infringement is still lacking, opening up opportunities for abuse.